Information management strategy implementation in organizations / Muhammad Azhar Mohamad ... [et al.] - Mohamad, Muhammad Azhar; Mat Yatin, Saiful Farik; Adha Zahir, Muhammad Izzat; Syed Hilmi, Syed Hisham Shah (Faculty of Information Management, 2022)
This paper explains the implementation of information management strategy in the organization. The term "information strategy" refers to the management and use of "information" as a strategic resource. In the strategy hierarchy, information strategy might be integrated with the organization's strategic plan. Information-based activities now occupy a significant amount of the workforce and are becoming increasingly vital to the success of organizations and the efficiency of administrations. This paper evaluates the information strategies implementation, explores previous studies, planning for productivity, discussion, and conclusion on the topic for further studies.